Essentials of store-keeping and purchasing (TYBCom) - Varma M.M. and Seth R.K. (Sultan Chand, New delhi, 2001)
Commerce
ENGLISH
Keywords: Essentials of store-keeping and purchasing (TYBCom); Commerce; Commerce